2023
DOI: 10.1108/jed-11-2022-0231
|View full text |Cite
|
Sign up to set email alerts
|

Institutional quality and economic growth in Sub-Saharan Africa: a panel data approach

Mohammed Seid Hussen

Abstract: PurposeThe main purpose of this study is to examine the impact of different dimensions of institutional quality indices on the economic growth of Sub-Saharan African (SSA) countries.Design/methodology/approachThe study uses a panel data set of 31 SSA countries from 1991 to 2015 and employs a two-step system-GMM (Generalized Method of Moments) estimation technique.FindingsThe study's empirical results indicate that investment-promoting and democratic and regulatory institutions have a significant positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…From the fixed effects and random effects methods of estimation utilized in the study, they found that institutional quality has a positive impact on the economic growth of East African countries. Their study strictly recommended the improvement in institutional quality in East Africa [ 2 , 3 , 53 ].…”
Section: Reviews Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…From the fixed effects and random effects methods of estimation utilized in the study, they found that institutional quality has a positive impact on the economic growth of East African countries. Their study strictly recommended the improvement in institutional quality in East Africa [ 2 , 3 , 53 ].…”
Section: Reviews Of Related Literaturementioning
confidence: 99%
“…In Africa, the link between fiscal policy variables, institutional quality, and economic growth become the focus of policy makers following agenda 2063. Consequently, several empirical studies linked intuitional quality and growth in SSA countries and reported a positive relationship [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, 45-50% of the population is impoverished (Solarin et al, 2021;Osinubi, 2005). More people live in abject poverty on the continent than on any other continent on the planet (Hussen, 2023;Solarin et al, 2021;Ndlovu and Toerien, 2020). Over the last few decades, SSA has remained the only region on the planet to see an increase in extreme poverty (Olaoye and Zerihun, 2023;Alpay, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, 45–50% of the population is impoverished (Solarin et al ., 2021; Osinubi, 2005). More people live in abject poverty on the continent than on any other continent on the planet (Hussen, 2023; Solarin et al. , 2021; Ndlovu and Toerien, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the instruments of achieving macroeconomic objectives such as controlling the level of inflation and unemployment. Furthermore, government revenue is considered a tool for enhancing social justice and poverty alleviation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%